2010
DOI: 10.1002/mats.200900051
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide‐Mediated Radical Polymerization in Dispersed Systems: Compartmentalization and Nitroxide Partitioning

Abstract: Cover: The image presents the relaxation of a melt of dense polymer globules into a standard entangled melt. Short chains expand isotropically in space while very long chains relax by reeling out ends, as illustrated by the timedependent ratio of the squared end-to-end distance and radius of gyration (inset). Further details can be found in the article by T. Vettorel and K. Kremer* on page 44. Contents Growing Interest in Theory and Simulations S. SpiegelMacromol. Theory Simul. 2010, 19, 7-9 Full Paper: Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The details of the modeling approach used to investigate compartmentalization effects in NMP have been fully described in previous papers and will not be repeated here 18, 23, 24. In short, the modified Smith–Ewart equations describe the number fractions of particles $N_{i}^{j} $ (particles containing i P • and j T • ): where N A is the Avogardo's number and v p is the particle volume.…”
Section: Modeling and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the modeling approach used to investigate compartmentalization effects in NMP have been fully described in previous papers and will not be repeated here 18, 23, 24. In short, the modified Smith–Ewart equations describe the number fractions of particles $N_{i}^{j} $ (particles containing i P • and j T • ): where N A is the Avogardo's number and v p is the particle volume.…”
Section: Modeling and Simulationsmentioning
confidence: 99%
“…CLRP in dispersed systems14, 15 can under certain circumstances be strongly influenced by the phenomenon of compartmentalization, which refers to the physical isolation of reactants in discrete confined spaces, i.e., the monomer droplets or polymer particles. Effects of compartmentalization have been predicted theoretically for NMP,16–24 atom transfer radical polymerization (ATRP),22, 25–28 and reversible addition‐fragmentation chain transfer (RAFT) polymerization,21, 22, 29–32 and experimental evidence is also starting to emerge 33–36. There are two possible distinct effects of compartmentalization: The segregation effect and the confined space effect 14, 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the nature of the nitroxide influenced the minimum particle size beyond which compartmentalization could not be neglected. Subsequently, Zetterlund [115] reviewed and also presented new results on compartmentalization and nitroxide partitioning effects. In this work, they implemented a model in Predici to predict the partitioning of the nitroxide between phases.…”
Section: Nmp In Heterogeneousmentioning
confidence: 99%
“…The purpose of this review is to provide a brief account of the progress in computer simulations of polymerization reactions in confined geometries and on surfaces. Because recent reviews have dealt in depth with in silico polymerization in confined spaces,9–11 we will concentrate primarily on the class of macromolecules prepared by direct polymerization from surfaces. We will revisit briefly some aspects of the various methods that have been applied to describe polymerization reactions in bulk and point out how some of those approaches can be adopted in the so‐called “grafting from” polymerizations.…”
Section: Introductionmentioning
confidence: 99%